Strategi Komunikasi Dinas Lingkungan Hidup (DLH) Kota Padang Dalam Meningkatkan Kesadaran Masyarakat Pada Pencegahan Pencemaran Air Sungai Batang Arau - Brata Nurhadi; Ria Edlina (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2025)
This study aims to analyze the communication strategy implemented by the Padang City Environmental Agency (DLH) in increasing public awareness about preventing water pollution in the Batang Arau River. The Batang Arau River is one of the important water resources in Padang City that faces pollution problems due to industrial waste and domestic waste activities. Using a qualitative method with a descriptive approach, data were collected through in-depth interviews with DLH officials, field observations, and documentation. Data analysis was carried out through data reduction, data presentation, and drawing conclusions. The results show that the Padang City DLH implemented a persuasive communication strategy through direct approaches such as socialization, counseling, and community-based education, as well as indirect approaches through social media, billboards, and environmental campaigns. The communication strategy applied refers to a participatory communication model by involving community leaders, river care communities, and educational institutions. Obstacles found were a lack of public awareness, budget limitations, and low consistency of supervision. In conclusion, the Padang City DLH communication strategy is quite effective in increasing public awareness, although it still requires strengthening in the aspects of active community participation and cross-sector collaboration. This research is expected to provide input for the development of more innovative, sustainable, and community participation-based environmental communication strategies.